Keeping It Simple, Transport Mechanism and pH Regulation in Na(+)/H(+) Exchangers - Călinescu, Octavian (American Society for Biochemistry and Molecular Biology, 2014)
Na(+)/H(+) exchangers are essential for regulation of intracellular proton and sodium concentrations in all living organisms. We examined and experimentally verified a kinetic model for Na(+)/H(+) exchangers, where a single binding site is alternatively occupied by Na(+) or one or two H(+) ions. The proposed transport mechanism inherently down-regulates Na(+)/H(+) exchangers at extreme pH, preventing excessive cytoplasmic acidification or alkalinization. As an experimental test system we present the first electrophysiological investigation of an electroneutral Na(+)/H(+) exchanger, NhaP1 from Methanocaldococcus jannaschii (MjNhaP1), a close homologue of the medically important eukaryotic NHE Na(+)/H(+) exchangers. The kinetic model describes the experimentally observed substrate dependences of MjNhaP1, and the transport mechanism explains alkaline down-regulation of MjNhaP1. Because this model also accounts for acidic down-regulation of the electrogenic NhaA Na(+)/H(+) exchanger from Escherichia coli (EcNhaA, shown in a previous publication) we conclude that it applies generally to all Na(+)/H(+) exchangers, electrogenic as well as electroneutral, and elegantly explains their pH regulation. Furthermore, the electrophysiological analysis allows insight into the electrostatic structure of the translocation complex in electroneutral and electrogenic Na(+)/H(+) exchangers.